Health Information and Decision Making Preference on Disease Treatment - Muhammad Hasif Bin Mohamed Ali (Althea Medical Journal, 2015)
Background: Medical decision making is a complex cognitive process of choosing in establishing a diagnosis and selecting a management option in the context of healthcare. Patients may desire to take part in obtaining and exchanging information, discussing over options and making the final decisions about treatment and or care. The focus of the study was to identify the health information and decision making preference on diseases treatment.